2021
DOI: 10.20944/preprints202107.0043.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitogenome Phylogeny Including Data from Additional Subspecies Provides New Insights into the Historical Biogeography of the Eurasian lynx Lynx lynx

Abstract: Phylogenetic and phylogeographic assessments of species should ideally include individuals of all known populations. However, this is difficult for species with large distribution areas. Previous molecular studies of the wide-ranging Eurasian lynx Lynx lynx focused mainly on its northern Palearctic populations, with the consequence that the reconstruction of this species’ evolutionary history did not include genetic variation present in its southern Palearctic distribution. We sampled a previously no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Moreover, an understudied Eurasian lynx population in south-western Turkey, which might represent another remnant population of the Balkan lynx subspecies (Cömert et al 2018;Mengüllüoğlu et al 2021a), could be another candidate source for population rescue and needs special attention from both the ecological and genetic point of view. Previous studies, however, showed that this lynx population occur in montane coniferous forests and at very high densities with brown hare as its principal prey (Avgan et al 2014;Mengüllüoglu et al 2018), suggesting it is ecologically more similar to other Caucasian lynx populations in Anatolia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, an understudied Eurasian lynx population in south-western Turkey, which might represent another remnant population of the Balkan lynx subspecies (Cömert et al 2018;Mengüllüoğlu et al 2021a), could be another candidate source for population rescue and needs special attention from both the ecological and genetic point of view. Previous studies, however, showed that this lynx population occur in montane coniferous forests and at very high densities with brown hare as its principal prey (Avgan et al 2014;Mengüllüoglu et al 2018), suggesting it is ecologically more similar to other Caucasian lynx populations in Anatolia.…”
Section: Discussionmentioning
confidence: 99%
“…The evolutionary history of the Balkan lynx lineage stretches for more than 50 kya years (Mengüllüoğlu et al 2021a;Bazzicalupo et al 2022) and, during this time, its population has always been relatively small compared to other populations in Asia, or Europe (Bazzicalupo et al 2022). Given the long-term process of inbreeding, it is likely that reproductive success is already affected by inbreeding depression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Archival and non-invasively collected sample material is increasingly utilized in molecular studies of wildlife species, particularly if these are rare, elusive, protected, or inhabit areas that are difficult to access (e.g. Paijmans et al, 2020; Mengüllüoglu et al 2021; Hessels et al 2021; Sacks et al 2021; von Thaden et al 2021; Cho et al 2022). DNA extracted from such material is usually highly degraded, rendering downstream analyses difficult (e.g.…”
Section: Introductionmentioning
confidence: 99%